Soft tissue aneurysmal bone cyst in thigh muscles: A case report - Hossein Bozorgi; Behzad Aminzadeh; Amir Mahmoud Ahmadzade; Farzane Khoroushi; Mostafa Izanlu (Clinical Case Reports, 2022)
Abstract Aneurysmal bone cysts (ABCs) are benign lesions that are locally invasive. The prevalence of soft tissue ABCs is far lower than the intraosseous type. Here, we report a case of ABC in thigh muscles who presented with distal thigh pain.